2020
DOI: 10.1186/s12871-020-01148-x
|View full text |Cite
|
Sign up to set email alerts
|

How does intraarticular dexmedetomidine injection effect articular cartilage and synovium? An animal study

Abstract: Background Intraarticular injections are widely used to provide pain relief after arthroscopic procedures and minimize the use of opioids. Dexmedetomidine has been proven to potentiate pain relief and postpone the demand for the first analgesic drug when it is used intraarticularly following arthroscopic knee procedures. However, the effects of dexmedetomidine on articular structures have not yet been evaluated. Our aim was to determine the effects of intraarticular dexmedetomidine injection on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…In rats, administration of 25 ug of dexmedetomidine into the knee joint did not appear to have detrimental effects on histopathological parameters. 15 Although there are no in vivo studies describing the effects of α 2 -adrenergic agonists on joint structures following administration to horses, the effects of dexmedetomidine on equine chondrocytes in vitro have been described. 16 Mancini and colleagues 16 reported that exposure to dexmedetomidine impaired mitochondrial and lysosomal functions, altered cell membrane integrity, and induced late apoptosis and necrosis in the joint.…”
Section: Discussionmentioning
confidence: 99%
“…In rats, administration of 25 ug of dexmedetomidine into the knee joint did not appear to have detrimental effects on histopathological parameters. 15 Although there are no in vivo studies describing the effects of α 2 -adrenergic agonists on joint structures following administration to horses, the effects of dexmedetomidine on equine chondrocytes in vitro have been described. 16 Mancini and colleagues 16 reported that exposure to dexmedetomidine impaired mitochondrial and lysosomal functions, altered cell membrane integrity, and induced late apoptosis and necrosis in the joint.…”
Section: Discussionmentioning
confidence: 99%
“…7 DEX is receiving lot of attention as drug of choice. 8 Al-Metwalli and colleagues evaluated the prospective pain relief influence of DEX when given through intra articular route and concluded that DEX enhanced post-operative analgesia. 9 The drugs used in treatment of arthritis are usually given by oral, subcutaneous, and intramuscular routes.…”
Section: Introductionmentioning
confidence: 99%
“…Action potentials can move through axons, dendrites, and muscle tissue owing to sodium channels that are membrane proteins. One large alpha subunit and one or two small beta subunits make up sodium channels in various tissues [13]. All three local anaesthetic binding and ion conduction sites have four domains with six alphahelical membrane-spanning segments.…”
Section: Introductionmentioning
confidence: 99%